Students’ Scientific Explanation in Blended Physics Learning with E-Scaffolding - Oktavianti, E.; Handayanto, S. K.; Wartono, W.; Saniso, E. (Jurnal Pendidikan IPA Indonesia, 2018)
This purpose of this research was to analyze the influence of blended physics learning with e-scaffolding on the gas kinetic theory to the students’ scientific explanation. This research used quasi-experimentation with one group pretest-posttest design. The population of this research included the grade XI students of Natural Sciences in SMA Negeri 1 Bangkalan. The proposed hypothesis was that the blended physics learning with e-scaffolding affected the students’ scientific explanation. The research results indicated that the students’ scientific explanation ability significantly increased after they experienced blended physics learning with e-scaffolding. All aspects of scientific explanation, that was the claim, evidence, and reasoning improved significantly.